Improved climate-resilient rice varieties for Colombia - Fedearroz 68 for rainfed rice systems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Ex-post assessments already indicated its adoption by 9.09% (1,460) of rice growers in Colombia. See OICR #3844.